KESADARAN HUKUM MASYARAKAT TERHADAP PERKAWINAN DIBAWAH UMUR DITINJAU DARI UNDANG-UNDANG NO. 16 TAHUN 2019 TENTANG PERUBAHAN UNDANG-UNDANG NO. 1 TAHUN 1974 TENTANG PERKAWINAN - Neng Hilda Febriyanti; Anton Aulawi (Pendidikan Pancasila dan Kewarganegaraan, FKIP, Universitas Banten Jaya, 2021)
ABSTRACT This study aims to determine the level of legal awareness of the community in Pamengkang Village, Kramatwatu District, Serang Regency about underage marriage in terms of Law No. 16 of 2019 concerning Amendments to Law No. 1 of 1974 concerning Marriage. The approach used in this study is a qualitative approach. Qualitative research is research that describes, describes what is seen, heard, felt, and asked. The data collection techniques that will be carried out by researchers in this study are structured observation, interviews and documentation. The results of this study are that underage marriages in Pamengkang Village, Kramatwatu District, Serang Regency are still occurring due to several factors, namely, traditional factors or local customs, concerns about community gossip when their daughter becomes an old maid (late in marriage) if not married at a young age, weak economic factors, unemployment, low education and school dropouts. This shows that the Pamengkang Village Community is not aware of the law or the level of awareness and legal compliance is still low, especially awareness of the age limit for marriage as regulated in the Marriage Law by not having an underage marriage. Factors that contribute to the lack of awareness and legal compliance of the Pamengkang Village community with the Marriage Law and not having underage marriages are due to factors of education, habit of disobeying the law and lack of socialization and legal counseling of the Marriage Law and the risks of underage marriage by the Government concerned. . Keywords: legal awareness, underage marriage